The 4b-4c loop of excitatory amino acid transporter 1 containing four critical residues essential for substrate transport. Issue 12 (12th August 2020) - He, Suifen; Zhang, Wenlong; Zhang, Xiuping; Xu, Pingyi; Hong, Mei; Qu, Shaogang
Abstract: In the mammalians, the 4b-4c loop of excitatory amino acid transporters (EAATs) spans more than 50 amino-acid residues that are absent in glutamate transporter homologue of Pyrococcus horikoshii (GltPh ). This part of insertion is unique for metazoans and indispensable to the localization of EAATs. The excitatory amino acid transporter (EAAT) 1 is one of the two glial glutamate transporters, which are responsible for efficiently clearing glutamate from the synaptic cleft to prevent neurotoxicity and cell death. Although the crystal structure of EAAT1cryst (a human thermostable EAAT1) was resolved in 2017, the structure-function relationship of the 4b-4c loop has not been elucidated in EAAT1cryst . To investigate the role of the 4b-4c loop, we performed alanine-scanning mutagenesis in the mutants and observed dramatically decreased transport activities in T192A, Y194A, N242A, and G245A mutants. The surface expression of T192A and Y194A mutants even decreased by more than 80%, and most of them were detained in the cytoplasm. However, when T192 and Y194 were substituted with conservative residues, the transport activities and the surface expressions of T192S and Y194F were largely recovered, and their kinetic parameters (Km values) were comparable to the wild-type EAAT1 as well. In contrast, N242 and G245 substituted with conservative residues could not rescue the uptake function, suggesting that N242 and G245 may play irreplaceable roles in the glutamate uptake process. These results indicate that the 4b-4c loop of EAAT1 may not only affect the glutamate uptake activity, but also influence the surface localization of EAAT1 by T192 and Y194. Communicated by Ramaswamy H. Sarma